Clinical evaluation of all-ceramic crowns - (:unkn) unknown (MOSBY-ELSEVIER, 2002)
Statement of problem. There are few in vivo studies on the clinical performance of all-ceramic crowns. Purpose. The aim of this study was to evaluate the clinical performance of IPS Empress crowns. Material and methods. Thirty-seven all-ceramic IPS Empress crowns were placed in 20 patients. Twenty crowns were luted with Variolink II low-viscosity resin cement in combination with Syntac Classic dentin adhesive; the remaining 17 were luted with Variolink II in combination with Syntac Single Component. All procedural steps were performed by the same prosthodontist. Using the California Dental Association's (CDA) quality evaluation system, 2 calibrated evaluators examined the crowns for margin integrity, anatomic form, surface, and color for a period of 12 to 41 months, with a mean of 24.56 months after insertion. Kaplan-Meier statistical analysis was used to calculate the survival rate of the crowns. Values obtained for plaque and gingival conditions were compared to control teeth with use of the Wilcoxon signed ranks test (P<.05). Results. Based on the CDA criteria, 94.6% of the crowns were rated satisfactory. Fracture was registered in only I crown. One endodontically treated tooth failed due to the dislodgement of the prefabricated dowel. No significant difference was observed in the gingival health status of crowns that had margins placed above or at the level of the gingival margin. However, in crowns that had subgingival margin finish lines, the percentage of bleeding on probing was significantly higher than that of the contralateral control teeth. Conclusion. In this in vivo study, IPS Empress crowns luted with both dentin bonding agents functioned satisfactorily with a relatively low fracture rate over a mean evaluation period of 24.56 months.
Keywords: FRACTURE-TOUGHNESS; GENERAL-PRACTICE; DENTAL CERAMICS; BOND STRENGTHS; EMPRESS; SYSTEMS; DICOR